Struktur Anatomi Kayu Meranti Tembaga (Shorea leprosula Miq.) pada PT. Dwima Jaya Utama: Anatomical Structure of Meranti Tembaga (Shorea leprosula Miq.) at PT. Dwima Jaya Utama - Joni, Herwin; Wahyudi, Wahyudi; Sosilawaty, Sosilawaty; Santoso, Mahdi; Toni, Hendra; Triyadi, Antonius; Aguswan, Yusuf (HUTAN TROPIKA, 2024)
This study analyzes the quality of  meranti tembaga wood from natural forests with a maximum diameter of 50 cm as a material for the timber management industry. Furthermore, the study also examined the quality of meranti tembaga wood (Shorea leprosula Miq.) from silin engineering plants with diameters of 28 cm, 36 cm, 43 cm, and 51 cm.  This study also examines the diversification of the use of copper meranti wood from silin engineering plants to explore the potential applications of this wood in various industries. Meranti tembaga wood samples were taken from natural forests and plantation forests (intensive silviculture/silin) of PBPH PT Dwimajaya Utama, Central Kalimantan. Furthermore, wood anatomy testing was carried out at the Forest Hasi Technology Laboratory, Gadjah Mada University. The quality of Copper meranti wood from natural forests with a minimum diameter of 50 cm for the wood processing industry was studied. The results of the analysis of the quality of  meranti tembaga wood from Silin engineering plants showed significant variations based on diameter. For a diameter of 28 cm, the cell wall thickness is 1.675 and the lumen diameter is 22.752. For a diameter of 36 cm, the cell wall thickness is 1,633 and the lumen diameter is 20,739. For a diameter of 43 cm, the cell wall thickness is 1.592 and the lumen diameter is 2.268. For a diameter of 51 cm, the cell wall thickness is 1,738 and the lumen diameter is 21,066.